Board of Directors and Earnings Quality in Chinese Manufacturing Listed Companies - Chi, X (2016)
This paper is about to examine the relationship between corporate governance characteristics from the perspective of board of directors and earnings quality based on the data collected from China Stock Market and Accounting Research (CSMAR) covers all Chinese manufacturing listed companies from the year 2012 to 2015, except those companies with missing data. With the help of Jones model to get the abnormal accruals of those companies. After descriptive analysis, regression analysis, we know that there is a significant relationship between board of directors and earnings quality.